The role of teachers’ perceptions for inclusive teaching: why plan teacher education on simplex theory? - Aiello, Paola; Sharma, Umesh; Sibilio, Maurizio (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
This work presents an interpretation of the construct of agency proposed by Albert Bandura from a simplex perspective within the field of inclusive education. The thesis proposed acknowledges the proactive role of the teacher in choosing teaching strategies aimed at guaranteeing school achievement of all students independent of their needs and abilities. It highlights the teachers’ perceptive mechanisms that intervene during the didactic transposition. The objective is that of proposing teacher education courses that are based on reflectiveproactive training paths and are oriented towards teacher cognisance of their own resources and their transformative and generative potential.